Characterising KandyPens-related posts to Instagram: implications for nicotine and cannabis use. Issue 4 (30th May 2019) - Majmundar, Anuja; Kirkpatrick, Matthew; Cruz, Tess Boley; Unger, Jennifer B; Allem, Jon-Patrick
Abstract : Background: This study analysed posts to Instagram related to KandyPens, an open-system pod mod e-cigarette company, marketing its products as aromatherapy devices. The objective was to determine themes, corresponding user profiles and references to types of e-liquid solutions used with KandyPens. Methods: Data consisted of publicly available posts to Instagram with the hashtag '#kandypens' collected from 8 June to 8 August 2018 (n=1775). Identified themes included: product appearance (eg, highlighting design features including colour of device), user experience (eg, vape tricks), flavours (eg, strawberry) and promotions (eg, $10 off). The type of e-liquid solutions (nicotine, aromatherapy and cannabis) used with KandyPens were also recorded. Instagram profiles were categorised into: vaping enthusiast/advocates, influencers, KandyPens' official Instagram account, vape vendors and average Instagram users . Results: User experience (28.90%) and product appearance (21.80%) were predominant themes followed by promotions (10.08%), and flavours (1.01%). About 32.43 % of posts referenced cannabis-related solutions, 2.98 % of the posts mentioned nicotine-related solutions and 0.11 % of the posts mentioned aromatherapy. Average Instagram users (24.89%) posted the majority of posts followed by vape vendors (20.72%), KandyPens' official account (17.96%), vaping enthusiasts/advocates (10.75%) and influencers (0.45%). Conclusion: KandyPens markets its products as aromatherapy devices; however, Instagram posts related to these products rarely mentioned their purported purpose. Future research should consider product design, user experience and the co-use of nicotine and cannabis with KandyPens to assess implications related to product appeal and abuse liability.